EFFICIENT LIGHTWEIGHT CONCRETE BASED ON POROUS AGGREGATES - Akhmedov Islombek; Umarov Isroil; B.Sharopov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. This article discusses the experience of using lightweight aggregates. Due to the difficulty of producing expensive aggregates, this problem forces us to turn to the use of new types of porous aggregates using local raw materials and coal mining waste in lightweight concrete.